A Study of the History of Chinese Philosophy in Independent Ukraine: The Sinological Experience of Kyiv Universities in the Late 20th and Early 21st Centuries - Heorhii Vdovychenko (International Society of Philosophy and Cosmology, 2021)
The article deals with the achievements of the development of domestic studies on the history of philosophical education, science and culture of China in the Kyiv universities of independent Ukraine. The thirtieth anniversary of the beginning of the entry of independent Ukraine, after the final collapse of the USSR in 1991, to world socio-political life as its full participant, is celebrated this year. This year, at the same time, marks a historic starting point for a qualitatively new stage of bilateral relations between Ukraine and the People's Republic of China. A search of the history of China's philosophy by Ukrainian scholars from the A. Yu. Krymskyi Institute of Oriental Studies of the National Academy of Sciences of Ukraine and the H. S. Skovoroda Institute of Philosophy of the National Academy of Sciences of Ukraine, as well as from a number of other relevant institutes, is extremely important in the growing cooperation of academic science and universities of these two countries. It is noteworthy that the significant contribution to this process of leading Ukrainian Orientalists V. Kiktenko, S. Kapranov and their colleagues from these institutes is closely linked with important achievements in the development of philosophical Chinese studies in a number of universities in the capital of Ukraine, such as the Taras Shevchenko National University of Kyiv and Borys Grinchenko Kyiv University. The high scientific potential of V. Rezanenko, N. Kirnosova, O. Boichenko, G. Bokal, Y. Shekera, and some other Sinologists from the Institutes of Philology of both these universities and their other units, as well as the potential of their colleagues from the National University of "Kyiv-Mohyla Academy," Vadym Hetman Kyiv National Economic University, the Kyiv National Linguistic University, is distinctly reflected in the proceedings of symposia and in the periodicals of the said universities.